Clarification technologies for monoclonal antibody manufacturing processes: Current state and future perspectives. Issue 4 (29th September 2015) - Singh, Nripen; Arunkumar, Abhiram; Chollangi, Srinivas; Tan, Zhijun George; Borys, Michael; Li, Zheng Jian
ABSTRACT: Considerable progress has been made increasing productivity of cell cultures to meet the rapidly growing demand for antibody biopharmaceuticals through increased cell densities and longer culture times. This in turn has dramatically increased the burden of process and product related impurities on the purification processes. In addition, current trends in the biopharmaceutical industry point toward both increased productivity and targeting smaller patient populations for new indications. Taken together, these developments are driving the industry to explore alternative separation technologies as a future manufacturing strategy. Clarification technologies well established in other industries, such as flocculation and precipitation are increasingly considered as a viable solution to address this bottleneck in antibody processes. However, several technical issues need to be fully addressed including suitability as a platform application, robustness, process cost, toxicity, and clearance. This review will focus on recent efforts to incorporate new generation clarification technologies for mammalian cell cultures producing monoclonal antibodies as well as challenges to their implementation supported by a case study. Biotechnol. Bioeng. 2016;113: 698–716. © 2015 Wiley Periodicals, Inc. Abstract : This review paper focuses on recent efforts to incorporate new generation clarification technologies for mammalian cell cultures producing monoclonal antibodies as well as challenges to their implementation. Implementing the strategies discussed can address the bottleneck in antibody purification processes, enable fully disposable single‐use technologies and reduce the process footprint. However, there are several technical issues and challenges that need to be fully addressed for a wider adoption of these technologies by the biopharmaceutical industry.